Asal-Usul Larangan Pernikahan Jawa-Sunda dan Dampak Sosialnya - Ramadani, Ajeng Ayu (Postgraduate Studies UIN Sunan Ampel Surabaya, 2026)
This study aims to examine in depth the myth of the prohibition of marriage between Javanese and Sundanese people, which remains alive in some people's memories. This myth is generally associated with the historical tragedy of the Bubat War that occurred in 1357 CE, a political event that later developed into a prolonged cultural trauma. Through a qualitative literature study approach and descriptive analysis of 20 relevant academic sources, this study found that this prohibition has no valid legal basis, either in the Indonesian Marriage Law or in Islamic law. From a fiqh perspective, this myth is categorized as 'urf fasid' because it contradicts the principle of the permissibility of inter-ethnic marriage. Nevertheless, this prohibition still has socio-psychological implications for Javanese-Sundanese couples, particularly in the form of pressures of cultural adaptation, challenges of intercultural communication, and conflicts with the entire extended family. In today's modern society, this myth shows a tendency to be deconstructed, along with the strengthening of rationality, pluralistic values, and the view that household harmony is determined more by the quality of communication and commitment of couples than by past historical fears.